Teachers’ perceptions on the use of technology in the teaching and learning at early childhood education level in Redcliff urban schools - Chindowe, Charity (Midlands State University, 2018)
This study investigated on teachers’ perceptions on the use of technology at early childhood education level in Kwekwe district. The study was necessitated by the recent advances in technology use in teaching and learning. The Descriptive survey design was used to collect data. The population of this study comprised of twelve primary schools in Redcliff circuit and thirty six early childhood educators. A sample of nine out thirty six early childhood educators were selected to answer the questionnaire while three out of twelve teachers-in-charge responded to the interview. The questionnaire and the interview were used to generate data. Questionnaires were completed by nine early childhood educators while three teachers- in- charge from the infant department responded to the interviews. From the study it emerged that computers and televisions are forms of technology that are widely used at early childhood level. The benefits of technology were also established as the ability of technology to motivate learners, providing hands on approach, and enabling learners to develop holistically, that is physically, intellectually, emotionally and socially. From the study challenges associated with use of technology were also highlighted and these included lack of developmentally appropriate technology for use at early childhood education level, lack of child sized materials and lack of computer literacy among early childhood educators. The study suggested overcoming these challenges through providing pre-service and in-service training to early childhood educators for them to be equipped with the necessary skills. The study also recommended that there is need for the government of Zimbabwe to help all primary schools to have adequate age appropriate technology/equipment as it was observed a serious challenge and to enforce use of technology on daily basis through an educational policy.